INTERAKSI DEMOKRATIS DALAM PEMBELAJARAN EKSPLORATIF MODEL HOTL-DI TIPE A FENOMENA NYIUR MELAMBAI - Falenty Claudia Matulessy; Christophil Medellu; Jimmy Lolowang (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2021)
Natural phenomena around form a religious experience in students. The variety of experiences and perceptions that are formed in the cognitive structure can be integrated with formal learning in the classroom in order to strengthen the context-concept relationship or improve individual misconceptions. The purpose of this research is to explore the concept and scientific process of the phenomenon of waving palm trees or coconut trees that swing when blown by the wind. This research uses qualitative and quantitative approaches. The research was carried out in the physics department of FMIPA Unima. The results showed that the involvement of mentors can build open communication between students in groups and between student mentors and the target group. Cooperation and democratic behavior can be seen when students carry out exploration activities well, so that this learning can realize learning activities to explore objects or contexts, concepts and scientific processes of waving palm phenomena.